Multi-Stakeholder Partnerships for Tribal Development in India: A Systematic Literature Review - Rai, Dileep Kumar (Journal of Educational Research and Policies, 2026)
As one of the signatory members of the Sustainable Development Goals (SDGs) 2030, India is committed to incorporating the 17 SDGs in its policy and programs. The total size and scale of our country mean that the success of the global goals, to a large extent, depends on progress made by India. NITI Aayog oversees implementation by ministries and coordinates with States for the achievement of developmental targets as enshrined in the SDGs. However, the ambitious targets set under SDG 2030 requires a multi - dimensional, concerted and coordinated effort for influencing at all levels, and that no stakeholder can effect long - term change in isolation or silos. Additionally, as the Government of India commits itself to advancing SDGs and its accountability towards social inclusion and equitable growth, development partnerships must be promoted among the key stakeholders to see the desired impact of SDGs at the national level. Building on this context and in alignment with the ‘SDG 17 – Partnership for the Goals’, the article synthesizes key findings from literature review on the situation of tribal community in India, various initiatives undertaken by key stakeholders, the potential role of multi - stakeholder partnership (MSP) for scaling the impact of development actions undertaken for tribal development. The research paper would be helpful for duty bearers, policymakers, academia, corporations, and development practitioners to broaden their perspective on integrating MSPs into program designs aimed at the development of tribal communities in India. Through this analysis, the article also aims to contribute to the ongoing discourse on why building multi - stakeholder partnerships is important for scaling the impact of development actions and as a transformative tool for advancing the SDGs.